Comportamento assintótico das p-funções de torção quando p tende a 1 - Shirley da Silva Macedo (2017)
In this work, we study the solution of the torsion problem (...) where (...) is a bounded N-dimensional domain, N (...) 2, with Lipschitz boundary and (...) is the p -Laplaciano operator in its two versions: local (classical) and non-local (fractional).